Ківерцівський національний природний парк «Цуманська пуща»: збереження вікових дерев - Джам, О. А.; Dzham, O. A. (Волинський національний університет імені Лесі Українки, 2012)
Розглянуто необхідність збереження трьох багатовікових дубів – ботанічної пам’ятки природи місцевого значення в с. Городище Ківерцівського району Волинської області, оскільки кожне вікове дерево – це пам’ятка природи. Старі дерева – це ще й пам’ятки культури. Це цікаві природні музеї, своєрідні лабораторії для вчених.Each century-old tree is a beautiful monument of the nature. Old trees are also the memorials of culture, living witnesses to the past historical events. They are interesting natural museums, laboratories of sorts for the scientists. All this explains the necessity of the preservation of three multicentennial oaks, the local botanical curio of the village of Gorodyshche Kivertsi district Volyn region.
Kivertsi Nаtional Nature Reserve «Tsuman' Virgin Forest»: the Preservation of Century-old Trees
Keywords: національний природний парк; охорона довкілля; вікові дерева; пам’ятки природи; national nature reserve; preservation of environment; century-old trees; nature monuments